PERBANDINGAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) DENGAN METODE DISKUSI KELAS X SMA NEGERI 1 MODEL MUARA BELITI TAHUN PELAJARAN 2018/2019 - Neli Yuliani; Ahmad Amin; Wahyu Arini (SILAMPARI JURNAL PENDIDIKAN ILMU FISIKA, 2019)
This thesis is entitled "Comparison of Learning Outcomes Between Student Physics Cooperative Learning Model Student Tesms Achievement Division (STAD) Type with Class X Discussion Method 1 SMA Muara Beliti 1 Year 2018/2019 Academic Year". The problem in this study is whether there is a comparison of Student Physics Learning Outcomes Between Cooperative Learning Model Student Tesms Achievement Division (STAD) model and Discussion Method in Class X Model Muara Beliti 1 High School 2018/2019 Academic Year ?. The type of research used is quantitative in the form of experimental research methods conducted by comparing the experimental group I and the experimental group II design of this study pre-test post-test. As a population of all class X students of SMA Negeri 1 Model Muara Beliti Academic Year 2018/2019, which consisted of 236 students consisting of 7 classes. Sampling was done randomly and as a sample of experimental class I class X.IPA.1, and as a class experiment II class X.IPA.2. Data collection is done by test techniques, namely pre-test and post-test. Then the collected data was analyzed using the t-test, based on the results of the t-test analysis with a real level of α = 0.05, obtained tcount> t table (2.20> 2.00), so it can be concluded that the results of student physics learning using Cooperative Learning Model Student Tesms Achievement Division (STAD) type is higher than the discussion method in Class X of Model Muara Beliti 1 High School in Academic Year2018/2019.